Ciliary abnormalities in respiratory disease. Issue 3 (March 1988) - Buchdahl, R M; Reiser, J; Ingram, D; Rutman, A; Cole, P J; Warner, J O
Abstract : One hundred and sixty seven children, ranging in age from 5 weeks to 16 years, with chronic upper or lower respiratory tract problems, or both, were investigated for ciliary dyskinesia. Abnormal ciliary function was found in 18 cases all of whom had chronic lower respiratory disease and most of whom also had upper respiratory problems. Fifteen of the 18 cases had reduced ciliary beat frequencies (less than 10 Hz) associated with dyskinesia and the other three showed apparent absence of ciliated cells. Of the 15 cases with reduced ciliary beat frequencies, ciliary ultrastructure was normal in seven cases but abnormal with missing dynein arms and occasional abnormalities of microtubular arrangement in eight. Respiratory symptoms in the perinatal period were more common in children with abnormal ciliary function and present in all those with ultrastructural abnormalities or absence of ciliated cells compared with 34 (26%) of 132 children, in whom symptoms were recorded, with normal ciliary function. This study would suggest that all children with unexplained chronic respiratory disease, in particular those with symptoms starting in the perinatal period, should be investigated for ciliary dyskinesia.